Characterization of Butanediol-Alginate Ester as Candidate of Hemodialysis Membrane - Choirul Amri; Mudasir Mudasir; Dwi Siswanta; Roto Roto (Universitas Gadjah Mada, 2015)
An ester of butanediol-alginate has been studied as a possible hemodialysis membrane. With 1,4-butanediol molar ratio of 0.1, 0.5, and 1.0, it showed that the membrane mechanical properties, stability, protein adsorption, platelet adhesion and performance for urea and creatinine clearance are better than that of unmodified alginate. The increase in 1,4-butanediol molar ratio causes hemodialysis ratio to improve, and causes protein adsorption and platelet adhesion at the membrane surface to decrease. In the case of protein adsorption and platelet adhesion, the membrane with the molar ratio of 1.0 has better hemocompatibility properties. In the hemodialysis test for 4 h, using 2.742 mg cm-2 h-1 of urea and 0.058 mg cm-2 h-1 of creatinine flux, this membrane showed that 48.5% of urea and 44.2% of creatinine were cleaned.